Effect of pre-deposited carbon layer on the formation of carbon nitride nanostructures prepared by radio-frequency plasma enhanced chemical vapour deposition - Khanis, Noor Hamizah; Ritikos, Richard; Othman, Maisara; Rashid, Nur Maisarah Abdul; Gani, Siti Meriam Ab; Muhamad, Muhamad Rasat; Rahman, Saadah Abdul (Elsevier, 2011)
Nanostructured carbon nitride (CN(x)) thin films were prepared by radio-frequency plasma enhanced chemical vapour deposition (rf-PECVD) on crystal silicon (c-Si) substrates coated with a layer of hydrogenated amorphous carbon (a-C:H). The a-C:H layer was deposited by rf-PECVD from the discharge of pure methane (CH(4)) while the nanostructures were formed from the discharge of a mixture of methane (CH(4)) and nitrogen (N(2)). The deposition rate, surface morphology and chemical bonding properties of the a-C: H films coating were studied with respect to the deposition time. The effects of these properties on the growth of CN(x) nanostructures were analyzed. The FTIR results indicated that the structure of the a-C:H layer was similar regardless of the thickness of the carbon layer. However, the length, diameter and vertical alignment of the nanostructures formed on the a-C: H layer were dependent on the thickness and surface morphology of the a-C:H coating the c-Si substrate. The a-C:H layer may have acted as a natural template for CN(x) nanostructure growth and the morphology of the a-C: H layer contributed to the formation of rigid, vertically aligned cylindrical shaped carbon nitride nanostructures. (C) 2011 Elsevier B.V. All rights reserved.